PENGARUH DIMENSI MOTIVASI BELANJA HEDONIS TERHADAP PEMBELIAN IMPULSIF ONLINE PADA SITUS MARKETPLACE TOKOPEDIA - Nugroho, Bagus; Idris, Idris (Faculty of Economics and Business Diponegoro University, 2018)
Tokopedia is one of the marketplace that stands in Indonesia. In January and March 2018 Tokopedia experienced a decrease in the number of visitors. This decrease in the number of visitors resulted in a decrease in Tokopedia sales as well. Thus, the Tokopedia marketing must carry out a strategy to increase its sales again. Impulsive buying are things that need to be considered to increase sales in Tokopedia.This research was conducted to find out what factors can increase impulsive buying in Tokopedia. Factors tested in this study include shopping adventure, value shopping, idea shopping, social shopping and relaxation shopping. Data collection was carried out by distributing questionnaires to 140 respondents who had shopped on Tokopedia. Sampling using non-probability method with convenience sampling approach. The analysis method uses multiple analysis techniques.The results shown in this study are motivations for adventure shopping, value shopping, and relaxation shopping with a significant positive effect on impulsive buying variables. Whereas for idea shopping motivation and social shopping is known to have no significant influence on impulsive buying.